Structural basis of astrocytic Ca2+ signals at tripartite synapses - Misa Arizono (Nature Portfolio, 2020)
Astrocytic Ca2+ signals can be fast and local, supporting the idea that astrocytes have the ability to regulate single synapses. Here, the authors report the organization of astrocytes at nanoscale level and identify nodes as a functional astrocytic component of tripartite synapses.